Development and psychometric testing of the satisfaction with Cultural Simulation Experience Scale. Issue 6 (November 2015) - Courtney-Pratt, Helen; Levett-Jones, Tracy; Lapkin, Samuel; Pitt, Victoria; Gilligan, Conor; Van der Riet, Pamela; Rossiter, Rachel; Jones, Donovan; Everson, Naleya
Abstract: Decreasing the numbers of adverse health events experienced by people from culturally diverse backgrounds rests, in part, on the ability of education providers to provide quality learning experiences that support nursing students in developing cultural competence, an essential professional attribute. This paper reports on the implementation and evaluation of an immersive 3D cultural empathy simulation. The Satisfaction with Cultural Simulation Experience Scale used in this study was adapted and validated as the first stage of this study. Exploratory factor analysis and confirmatory factor analysis were undertaken to investigate the psychometric properties of the scale using two randomly-split sub-samples. Cronbach's Alpha was used to examine internal consistency reliability. Descriptive statistics were used for analysis of mean satisfaction scores and qualitative comments to open-ended questions were analysed and coded. A purposive sample (n = 497) of second of nursing students participated in the study. The overall Cronbach's alpha for the scale was 0.95 and each subscale demonstrated high internal consistency: 0.92; 0.92; 0.72 respectively. The mean satisfaction score was 4.64 (SD 0.51) out of a maximum of 5 indicating a high level of participant satisfaction with the simulation. Three factors emerged from qualitative analysis: "Becoming culturally competent", "Learning from the debrief" and "Reflecting on practice". The cultural simulation was highly regarded by students. Psychometric testing of the Satisfaction with Cultural Simulation Experience Scale demonstrated that it is a reliable instrument. However, there is room for improvement and further testing in other contexts is therefore recommended. Highlights: Creating engaging simulations to support development of cultural competence is critical to patient safety. Satisfaction with the immersive 3D simulation experience was high. Three factors emerged from analysis: "Becoming culturally competent", "Learning from debrief" and "Reflecting on practice". The Satisfaction with Cultural Simulation Experience Scale is a reliable instrument.